Lipoprotein receptor interactions are not required for monocyte oxidation of LDL. - M K Cathcart; Q Li; G M Chisolm, 3rd (Journal of Lipid Research, 1995)
Upon activation, human peripheral blood monocytes and U937 cells oxidized low density lipoprotein (LDL), converting it to a cytotoxin. The oxidized LDL loses its ability to interact specifically with the native LDL (apoB/E) receptor and becomes a ligand for the scavenger receptors and two other receptors, Fc gamma RII (CD32) and CD36. We performed a series of studies to evaluate the potential contribution of each of these receptors to the process of monocyte-mediated LDL oxidation. To assess the participation of the apoB/E receptor, we tested the ability of activated human monocytes to oxidize LDL after up- and down-regulation of apoB/E receptors. Neither up-regulation nor down-regulation of the apoB/E receptor significantly modified the level of LDL lipid oxidation. Acetylated LDL, a ligand for scavenger receptors, was also oxidized by the activated monocytes. Methylated LDL, a chemically modified LDL that is not recognized by the apoB/E or scavenger receptors, was oxidized as well. Thus, LDL does not need to interact with either the apoB/E receptor or scavenger receptors in order to undergo lipid oxidation. Additionally, monoclonal antibodies to CD36 and CD32 were used to block these two receptors that recognize oxidized LDL. Although both antibodies interfered with oxidized LDL binding to these receptors, neither treatment interfered with LDL lipid oxidation mediated by activated human monocytes. Our results suggest that interaction with these receptors is not a requirement for LDL lipid oxidation by activated human monocytes.